2008
DOI: 10.1097/ccm.0b013e318170b82b
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation rescue for cardiopulmonary resuscitation in pediatric patients*

Abstract: ECPR successfully rescued some pediatric patients who failed rescue with conventional in-hospital CPR. Good neurologic outcomes were achieved in the majority of the survivors. Early cohort and post-ECPR renal failure were associated with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 50 publications
6
92
2
3
Order By: Relevance
“…Several pediatric studies have shown increased mortality rates for patients cannulated after 30 minutes of conventional CPR. 7,11,28,34 However, other retrospective studies [8][9][10]12,20,26,27,29,31,32 of pediatric patients have shown positive outcomes with median CPR duration of 30 to 50 minutes. Even more interesting are the multiple case reports 24,27,30,32,37 of successful cannulation and survival to discharge in patients receiving CPR of up to 90 to 220 minutes.…”
Section: Population Of Patientsmentioning
confidence: 95%
See 3 more Smart Citations
“…Several pediatric studies have shown increased mortality rates for patients cannulated after 30 minutes of conventional CPR. 7,11,28,34 However, other retrospective studies [8][9][10]12,20,26,27,29,31,32 of pediatric patients have shown positive outcomes with median CPR duration of 30 to 50 minutes. Even more interesting are the multiple case reports 24,27,30,32,37 of successful cannulation and survival to discharge in patients receiving CPR of up to 90 to 220 minutes.…”
Section: Population Of Patientsmentioning
confidence: 95%
“…Aharon et al 28 Alsoufi et al 21 Alsoufi et al 30 Cengiz et al 4 Chan et al 5 Chrysostomous et al 29 Conrad et al Delmo Walter et al 11 Duncan et al 22 Huang et al 13 Huang et al 9 Joffe et al 19 Kane et al 20 Kelly and Harrison 31 Kumar et al 12 No. (%) of survivors to discharge 8 (80) 23 (46) 27 (34) 64 (40) 208 (42) 30 (75) Neonatal: 65 (43) Pediatric:…”
Section: Referencementioning
confidence: 99%
See 2 more Smart Citations
“…Survival for pediatric patients has been reported as anywhere from 23 to 73% based on published, single-center experiences [174][175][176][177][178][179][180][181][182]. Two multicenter registry database analyses have also been performed.…”
Section: Advances In Cerebral Resuscitation In Childrenmentioning
confidence: 99%